2020
DOI: 10.1186/s12871-020-01173-w
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia departments’ readiness for the COVID-19 pandemic; a nationwide cross-sectional study in Israel

Abstract: Background The Coronavirus infectious disease 2019 (COVID-19) brings anesthesiologists and intensive care physicians to the mainstay of clinical workload and healthcare managements’ focus. There are approximately 900 anesthesiologists in Israel, working in non-private hospitals. This nationwide cross-sectional study evaluated the readiness and involvement of anesthesia departments in Israel in management of the COVID-19 pandemic. The impact on anesthesiologists’ health, workload, and clinical practices were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
1
1
2
Order By: Relevance
“…Despite current guidelines that encourage using VL, only 21% of Croatian hospitals use VL always, in routine intubation of COVID-19 patients. Compared to our results, Cohen et al reported that VL was the default device used in intubation of COVID-19 patients in 93% of anesthesia departments in Israel [ 36 ]. Single-center study from the UK found that 79% of all intubations of COVID-19 patients were done with VL [ 37 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Despite current guidelines that encourage using VL, only 21% of Croatian hospitals use VL always, in routine intubation of COVID-19 patients. Compared to our results, Cohen et al reported that VL was the default device used in intubation of COVID-19 patients in 93% of anesthesia departments in Israel [ 36 ]. Single-center study from the UK found that 79% of all intubations of COVID-19 patients were done with VL [ 37 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Un informe reciente enfatiza la amenaza inminente de la infección por COVID-19 para complicar el curso de los pacientes sometidos a cirugía. Al mismo tiempo, el riesgo de que los miembros del equipo quirúrgico infecten a los pacientes y al resto del personal es alto (11). La protección respiratoria es obligatoria durante la pandemia de COVID-19, incluso si la evidencia sobre la efectividad del EPP sigue siendo baja.…”
Section: Discussionunclassified
“…La extubación profunda puede ayudar a atenuar la respuesta de las vías respiratorias, pero deja el problema de un paciente anestesiado y una vía respiratoria desprotegida. Las guías de consenso recientes sobre este tema no sugieren el intercambio de vía aérea supraglótica segunda generación como una opción de primera línea en vista de la necesidad de un segundo procedimiento y la probabilidad de dificultad de la vía aérea después de su inserción (11,12).…”
Section: Extubaciónunclassified
“…It has been shown that anesthesiologists were at the leading front in the treatment of COVID-19 patients. 2 , 3 Initially, anyone caring for a COVID-19 suspected or confirmed patients were asked to comply with standard, contact, droplet and airborne precautions.…”
Section: Introductionmentioning
confidence: 99%